God was our pilot : surviving 33 missions in the 8th Air Force : the memoir of Bernard Thomas Nolan. - Nolan, Bernard Thomas (Homeland security and safety, 2020)
"In December 1943, Eisenhower was Supreme Commander of Allied forces in Europe with General Carl Spaatz in command of all US Army Air Force. In January 1944, M/G James Doolittle replaced M/G Ira Eaker to lead the Eighth Air Force. The air battle strategy scenario soon changed. Air strategy at the Casablanca Conference was to take out the Luftwaffe before D-Day. The modified P-51 was now one had in good numbers. Doolittle made a key decision to turn his fighters loose. They would no longer fly with bomber formation but now in fighter sweeps to hit Luftwaffe installations and destroy Luftwaffe fighters as they formed for the intercept. Spaatz and Doolittle prayed for one week of good weather in which massive bomber raids could be launched to flush out get German fighters. During that week, five such bomber attacks attacked key targets. It worked, but at high cost to both sides. Eighth Air Force, Fifteenth Air Force and the RAF lost 369 aircrafts, but the Luftwaffe Fighter Command lost an estimated two thirds of its strength. The Luftwaffe did not show up on D-Day except for a few furtive attacks on the beachheads. The battle for air supremacy was won by the Allies and the progressive decline of the Luftwaffe ensued thereafter. The book will provide insight into a pilot's mind who flew such missions and try to give the reader not only the historic background, but a sense of what it must have been like to fly such missions"--